Optimalisasi Kompetensi Perpajakan Guru-Guru SMK Melalui Pelatihan Pajak Penghasilan Pasal 21 Tarif Efektif Rata-Rata Dan Simulasi Coretax - Challen, Auliffi Ermian; Madjid, Suhirman; Asaari, Masagus; Elmanizar, Elmanizar; Jalilah, Muayyanah; Shefira, Shefira (JPM: Jurnal Pengabdian Masyarakat, 2026)
The Average Effective Rate is a new method for calculating Income Tax article 21, which will be implemented by the Indonesian government starting January 1, 2024. TER aims to simplify the process of calculating Income Tax Article 21 and make the taxation system more equitable. Additionally, at the beginning of 2025, the Directorate General of Taxes will implement an administrative service system called Coretax for all tax reporting purposes. The Directorate General of Taxes has conducted extensive outreach; however, it appears that many vocational school accounting teachers are unaware of the changes to Income Tax Article 21 regulations, the method for calculating Income Tax Article 21 using the Average Effective Rate method, and the process for reporting using Coretax. This community service program aims to provide new knowledge about Income Tax Article 21 using the Average Effective Rate method, to improve skills in calculating Income Tax Article 21 using the Average Effective Rate, and to acquire the skills to apply Coretax to create Income Tax Article 21 withholding slips and Income Tax Article 21 periodic tax return reports. This training activity was held at Yarsi University, serving as a concrete example of higher education institutions' contribution to improving the quality of teachers in the field of taxation. The tax training was attended by 36 teachers from various vocational schools in the Central Jakarta area. This community service activity ran smoothly and achieved its objectives. This is demonstrated by the results, which show that MGMP teachers have gained an increase in competence, specifically being able to calculate PPh 21 using the Average Effective Rate method and creating Income Tax Article 21 withholding slips and Income Tax Article 21 Periodic Tax Returns.